PENGARUH KEPRIBADIAN DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (Studi Pada Pegawai di Dinas Kesehatan Kabupaten Pati). - Ardhani Hestari Mahardika, 1342020017 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of personality on Job Satisfaction, influence Quality Work Life (QWL) on job satisfaction, the influence of personality on employee performance, the effect of Quality Work Life (QWL) to employee performance, the influence of personality on performance with the mediation of job satisfaction, and influence Quality Work Life (QWL) on the performance of the mediation and job satisfaction of employees in Pati District Health Office. The population in this study of employees at the District Health Office Pati were 106 people. The sampling technique in this study using census that took the entire population for the research sample. Data collected by questionnaire to be filled by the respondent. Analysis of the data by regression analysis and mediation. The results showed that personality significant positive effect on job satisfaction, Quality Work Life (QWL) significant positive effect on job satisfaction, personality significant positive effect on performance. Quality Work Life (QWL) significant positive effect on performance. Job satisfaction significant positive effect on performance. Job satisfaction does not mediate the effect of personality on performance. Job satisfaction does not mediate the effect of Quality Work Life (QWL) on performance.Keywords: Personality, Quality Work Life (QWL), job satisfaction and performance